ANALISIS MINAT KUNJUNGAN SISWA SMP DI MUSEUM GUNUNG API MERAPI YOGYAKARTA - , PUSPITA HERAWATI YUSMAR; , Pitaya, S.ET., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
An analysis of junior high school studentsâ interest in visiting the Merapi Volcano Museum Yogyakarta is a research that have to find out what the attraction is there in MGM that attract junior high school studentsâ to visited, and find out the benefits of the existence of MGM for junior high school studentsâ. MGM was founded as the educational museum that have to study the volcano and earthquake science. While this general knowledge about the perceived volcano is still lacking for the Indonesian people in general, and in especially for junior high school studentsâ. The museum invites the studentsâ to learn more about volcanoes, especially Mount Merapi. Using a questionnaire to collect data and then process them to graphs and tables. From the results of this questionnaire show that many junior high school studentsâ who visited the museum in the activities of school visits, and there are many junior high school studentsâ who do not know this museum. Collections owned by museums has drawn the attention and after a visit at the museum, junior high school studentsâ interested in coming back to MGM. With existence of this museum junior high school studentsâ gets a new science of volcanoes.